Multi-Beam Metasurface Control Based on Frequency Reconfigurable Antenna; [Ve? ?ar?ni metapovr?inski nadzor na podlagi frekven?no nastavljive antene] - Ismail M.M.; Qas Elias B.B.; Elwi T.A.; Bashar B.S.; Alanssari A.I.; Rhazali Z.A.; Misran H. (Society for Microelectronics, Electric Components and Materials, 2025)
This paper presents a new design and analysis of a reconfigurable antenna with a switchable slot held using PIN diodes for multifunction reconfiguration, including frequency multiplexing. The performance of the proposed antenna in terms of reflection coefficient spectra and radiation patterns is evaluated. From the results obtained, it is observed that the antenna can be operated for different frequencies: 1.8 GHz, 2.7 GHz, 3.1 GHz, 3.3 GHz, 4.1 GHz, 5.1 GHz, and 5.4 GHz. A maximum gain of 11.1 dBi is also significantly achieved at 5.1 GHz. Moreover, this antenna is designed to provide a high Q-factor and low-frequency ratio (FR) for using the spectrum efficiently. Upon the advantage of spatial diversity, multiple independent data streams can be transmitted over the same frequency simultaneously. All results obtained in this work were produced based on the simulation process using CST Microwave Studio simulator software at different switching scenarios. ? 2024 Society for Microelectronics, Electric Components and Materials. All rights reserved.